Exploring the impact of deepfake technology on public trust and media manipulation: A scoping review - Boediman, Eko Putra (Program Studi Ilmu Komunikasi, 2025)
Deepfake technology, an AI-driven method for synthesizing hyper-realistic yet fabricated content, has raised concerns regarding public trust and media manipulation. This scoping review examines its impact by analyzing interdisciplinary literature from computer science, communication, psychology, and sociology. Using a systematic review approach, the study identifies key trends, challenges, and research gaps. Findings reveal that deepfake technology significantly blurs the boundary between truth and fiction, eroding media credibility. Additionally, malicious actors exploit deepfakes to spread misinformation, manipulate public perception, and threaten information integrity. The study underscores the urgent need for increased awareness, policy interventions, and media literacy programs to mitigate deepfake-related risks. By mapping the current discourse, this review highlights critical areas for future research and practical strategies to safeguard digital information ecosystems.